Methods of Using the Principles of the Legal Society (Diversity Research: Journal of Analysis and Trends, 2023)
In this article, the importance of the principles of civil law, such as justice, honesty, honesty, rationality, in the application of law and judicial practice is scientifically analyzed. Issues of development of methodological bases of application of these principles, systematization of scientifically based approaches on their content and essence have been researched. Although the civil procedural law stipulates the evaluation of court decisions according to the criterion of fairness, it is critically analyzed that this requirement remains an abstract category. By comparing the ratio between legality and justice, it is justified that they are separate categories. Scientific ideas and solutions for the active and effective application of the principles of civil law in practice are offered.